2018
DOI: 10.1016/j.scitotenv.2018.05.109
|View full text |Cite
|
Sign up to set email alerts
|

Long-term and high-concentration heavy-metal contamination strongly influences the microbiome and functional genes in Yellow River sediments

Abstract: The world is facing a hard battle against soil pollution such as heavy metals. Metagenome sequencing, 16S rRNA sequencing, and quantitative polymerase chain reaction (qPCR) were used to examine microbial adaptation mechanism to contaminated sediments under natural conditions. Results showed that sediment from a tributary of the Yellow River, which was named Dongdagou River (DDG) supported less bacterial biomass and owned lower richness than sediment from Maqu (MQ), an uncontaminated site in the upper reaches o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
95
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 294 publications
(107 citation statements)
references
References 68 publications
8
95
0
4
Order By: Relevance
“…The Ace (https://www.mothur.org/wiki/Ace) and Chao1 (https://www.mothur.org/wiki/Chao) indexes were used to represent the community abundance, while the Shannon (https://www.mothur.org/wiki/Shannon) and Simpson (https://www.mothur.org/wiki/Simpson) indexes were used to represent the species richness and diversity of the fungal community [43,44]. Additionally, the similarities analysis (ANOSIM) and heatmap analysis were calculated in the vegan package of R language [45,46] and the Unifrac distance calculation was performed for fungal beta diversity comparisons. The figures were generated using Origin 2019b (Origin Lab Corporation, Northampton, MA, USA).…”
Section: Data Analysesmentioning
confidence: 99%
“…The Ace (https://www.mothur.org/wiki/Ace) and Chao1 (https://www.mothur.org/wiki/Chao) indexes were used to represent the community abundance, while the Shannon (https://www.mothur.org/wiki/Shannon) and Simpson (https://www.mothur.org/wiki/Simpson) indexes were used to represent the species richness and diversity of the fungal community [43,44]. Additionally, the similarities analysis (ANOSIM) and heatmap analysis were calculated in the vegan package of R language [45,46] and the Unifrac distance calculation was performed for fungal beta diversity comparisons. The figures were generated using Origin 2019b (Origin Lab Corporation, Northampton, MA, USA).…”
Section: Data Analysesmentioning
confidence: 99%
“…The normality test was performed by Kolmogorov-Smirnov test for each trace metal; One-sample T-test was used to compare the concentrations of heavy metals in individual environmental media with background value; The inter group difference was compared with the independent sample T-test; Pearson correlation analysis was combined with principal component analysis (PCA) to identify the source of pollution. Prior to this, the validity of PCA was tested by Kaiser-Meyer-Olkin (KMO) values (>0.5) and Bartlett Sphericity test (p < 0.01) [12,19], All mathematical and statistical calculations were performed by Excel 2016, Origin 8.6 and SPSS 21.0, with sample distributions plotted using ArcGIS 10.2.…”
Section: Discussionmentioning
confidence: 99%
“…Compared to the water analysis, the relative concentrations of the heavy metals in sediment still indicated that Zn and Cd were at the extremes of the distribution; however, some differences were seen in the relative ranking of the other 4 metals. Heavy metals in sediments tend to be the result of long-term accumulation [12,13], while heavy metal contents in surface water more closely reflect contemporary pollution within the catchment, thus explaining the relative differences seen between water and sediments. Compared with sediments in other rivers (Table S4), the contents of Cu, Cr, Zn, Ni and Pb in the Songhua River were significantly lower than those in the Yangtze River (p < 0.01) [11], while the concentrations of heavy metals were higher than those in many major European rivers such as the Ebro River and Seine River [41,42].…”
Section: Concentrationmentioning
confidence: 99%
See 1 more Smart Citation
“…Total soil DNA was extracted following the instructions of E.Z.N.A ® soil (Omega BioTek, Norcross, GA, USA) with 1% gel electrophoresis, and NanoDrop2000 was used to examine the DNA concentration and purity. The DNA samples were stored at −80 • C [38,39].…”
Section: Dna Extractionmentioning
confidence: 99%